Violation of Good Corporate Governance Principles by The Board of Directors in Corporate Law: A Case Analysis of Pt Asuransi Jiwasraya (Persero) - Nana Kartika; Rahul Ardian Fikri; Marsa Zahirah Badzlin; Zahra Nabila; Anisa Dwi Fadila (CERED Indonesia Institute, 2025)
The case of PT Asuransi Jiwasraya (Persero) represents one of the largest financial scandals in the history of state-owned enterprises in Indonesia, illustrating the weak implementation of Good Corporate Governance (GCG) principles. The Board of Directors, as the governing organ of the company, plays a central role in corporate management and is required to perform its duties in accordance with the principles of transparency, accountability, responsibility, independence, and fairness. This study aims to analyze violations of GCG principles committed by the Board of Directors of PT Asuransi Jiwasraya (Persero) and their legal implications from a corporate law perspective. The research method employed is normative legal research using statutory and case approaches. The findings indicate that the Board of Directors of PT Asuransi Jiwasraya (Persero) committed serious violations of GCG principles through imprudent investment management, abuse of authority, and disregard for the prudential principle, resulting in substantial losses to the state. Therefore, law enforcement against the Board of Directors is essential as a form of protection for shareholder interests and public trust in state-owned enterprises.